Mud causes disaster? Study of the Italian operation at Guadalajara on March 8–23, 1937 - Majzner, Robert (Armia kontra natura, 2020)
In March 1937, the Italian voluntary corps CTV began an offensive operation towards Guadalajara. Its aim was to cut the Madrid connection with Valencia and thus to close the ring of encirclement around the capital of the republican Spain. The guarantee of success was to be surprise, the use of motorized infantry and the support of armored weapons and aviation. The errors of the Italian command, heavy rain and snowfall did not make it possible to achieve the assumed success and after 2 weeks the offensive was stopped.